Cover Feature: Generation of α‐Iminyl Radicals from α‐Bromo Cyclic N‐Sulfonylimines and Application to Coupling with Various Radical Acceptors Using a Photoredox Catalyst (Chem. Eur. J. 2/2018). Issue 2 (2nd November 2017) - Esumi, Naoto; Suzuki, Kensuke; Nishimoto, Yoshihiro; Yasuda, Makoto
Abstract : The generation of an α‐iminyl radical and its application to organic synthesis were successfully accomplished. An α‐iminyl radical was produced using a combination of visible‐light and photoredox catalysts and was used in various radical reactions to give the corresponding coupling products. Furthermore, atom transfer radical addition (ATRA) to olefins proceeded to provide the ATRA products. This process provides a mild and efficient method for the synthesis of cyclic N ‐sulfonylimine‐containing molecules that act as bioactive compounds and become the precursors in sultam synthesis. More information can be found in the Communication by Y. Nishimoto, M. Yasuda et al. onpage 312 .